"THE HEARING RESULTS IN OTOSCLEROSIS AFTER STAPEDOTOMY" - M. H. Baradaranfar P. Dabirmoghaddam (Acta Medica Iranica, 2004)
Otosclerosis is the most frequent cause of conductive hearing loss in patients with intact tympanic membrane. It can be treated by surgery with various techniques. Because of limited manipulation and comparably similar results, stapedotomy at present is preferred over other surgical techniques by most surgeons. Here we present the operative results of 114 otosclerotic patients who underwent stapedotomy between 1997-2002 in Rahnemoom hospital, Yazd and Amiralam hospital, Tehran. The aim of this study is to evaluate the efficacy and safety of stapedotomy in otosclerosis surgery. The average air-bone gaps of patients improved significantly from 41.82 db to 14.23 db after operation. Other hearing parameters of patients (including air conduction, bone conduction and speech discrimination score) also improved significantly. Permanent vertigo did not occur after operation and preoperative tinnitus resolved in 56 of 78 patients. Stapedotomy is a safe and effective modality for improving conductive hearing loss in otosclerotic patients.